Which of the branched-chain amino acids increases cerebral blood flow in hepatic encephalopathy? A double-blind randomized trial - Romeiro, Fernando Gomes [UNESP]; Ietsugu, Marjorie do Val [UNESP]; Franzoni, Letícia de Campos [UNESP]; Augusti, Laís [UNESP]; Alvarez, Matheus [UNESP]; Santos, Lívia Alves Amaral [UNESP]; Lima, Talles Bazeia [UNESP]; Koga, Kátia Hiromoto [UNESP]; Moriguchi, Sônia Marta [UNESP]; Caramori, Carlos Antonio [UNESP]; Silva, Giovanni Faria [UNESP]; Betting, Luiz Eduardo Gomes Garcia [UNESP] (Elsevier, 2018)
Branched-chain amino acids increase the brain perfusion of patients with hepatic encephalopathy (HE), but the amino acid and the mechanisms involved are still unknown. This study compared brain perfusion and clinical improvement during leucine or isoleucine supplementation. After randomization, 27 subjects with cirrhosis and HE received leucine or isoleucine supplements for one year. Brain single Photon Emission Computed Tomography (SPECT) and dynamic brain scintigraphy (DBS) were performed pretreatment and at 1, 8 and 12 months of supplementation. Brain perfusion was increased only in the isoleucine group at 8 months of treatment by both SPECT and DBS (p < 0.001 and p = 0.05, respectively) and by SPECT at the 12th month (p < 0.05). This was associated with hepatic encephalopathy improvement at 8 and 12 months (p = 0.008 and 0.004, respectively), which was not observed in the leucine group (p = 0.313 and 0.055, respectively). Isoleucine supplementation achieved a better impact on brain perfusion restoration in HE.
Keywords: Branched-chain amino acids; Cerebral blood flow; Hepatic encephalopathy; Liver cirrhosis